Saiyid Ahmad Shahid : his life and mission - Ahmad, Mohiuddin (Series (Academy of Islamic Research & Publications (Lucknow, India)), 1975)
On the life and mission of an Indian Muslim religiosocial reformer, Sayyid Ahmad, 1786-1831.